2020
DOI: 10.1002/pds.4960
|View full text |Cite
|
Sign up to set email alerts
|

Identifying drug combinations associated with acute kidney injury using association rules method

Abstract: Background: Older adults are at an increased risk of acute kidney injury (AKI) because of aging, multiple comorbidities, and polypharmacy.Objectives: The aim of this case-crossover study was to apply association rule (AR) analysis to ascertain drug combinations contributing to the risk of AKI in adults aged 65 years and older. Methods:We sourced a nationwide representative sample of New Zealanders aged ≥65 years from the pharmaceutical collections and hospital discharge information.Prescription records (2005)(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…In addition, ondansetron is approved in cancer patients and in the post-operative setting, implying the possibility of indication bias. However, a recent study examining drug combinations reported that ondansetron may increase the risk of AKI [36]. In patients receiving chemotherapy, GI symptoms may correlate with nephrotoxicity and thus it is di cult to say if an antiemetic is a marker or mediator of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ondansetron is approved in cancer patients and in the post-operative setting, implying the possibility of indication bias. However, a recent study examining drug combinations reported that ondansetron may increase the risk of AKI [36]. In patients receiving chemotherapy, GI symptoms may correlate with nephrotoxicity and thus it is di cult to say if an antiemetic is a marker or mediator of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…The National Minimum Data Set (NMDS) is a national collection of public and private hospital discharge information, including coded clinical data for inpatients and day patients. We have provided a detailed description of both the datasets previously 7,8 . We used unique encrypted National Health Index (NHI) identifiers to cross‐match medication exposure data with hospital events data from NMDS.…”
Section: Methodsmentioning
confidence: 99%
“…The control period is the l‐day period 36 days before the index date. We chose two 5‐week washout periods based on our previous study to avoid carrying over the effects of any medication exposures around the control period and to exclude prescriptions that are dated and unlikely to have effects within the observation period 8 . We calculated the duration of each prescription by dividing the total dose supplied by the daily dose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The local linear embedding algorithm converts the global nonlinear problem into a local linear problem by expressing the overall global structure information through the overlapping local neighborhoods. The global lowdimensional representation of the data points is obtained by regrouping each sample data point and its neighborhood after dimensionality reduction by some rules [10] . If for a given high-dimensional spatio-temporal large data set   A local reconstruction weight matrix is calculated from the nearest neighbors of the sample points, and the following error function is defined.…”
Section: 3dimensionality Reduction Of Highdimensional Spatio-temporal Big Datamentioning
confidence: 99%